Potential Risks for Seahorse Stock Enhancement: Insight From the Declivity of Genetic Levels With Hatchery Management - Luo, Wei; Wu, Qing; Zhang, Xiaoyang; Wei, Yuling; Liao, Min; Gao, Tong; Zhang, Yibo; Zhang, Shoudong; Chen, Pengyu; Guo, Zhonggang; Xiong, Yinlin; Xu, Zhou; et al. (Frontiers in Genetics, 2022)
Stock enhancement is one of the potential management strategies for the fishery. To better understand the impaction of stock enhancement, we simulated an experiment for lined seahorse (Hippocampus erectus) and evaluated the genetic structure after stock enhancement. In this study, we found the numbers of alleles (NA) and heterozygosity (HO) of stock enhancement strains were lower than those of the wild collections, while the inbreeding coefficient (FIS) and relatedness index were higher. Within the 3 generations of stock enhancement strain, the NA, HO and polymorphism information content (PIC) didn’t change significantly. In addition, the FST value indicated that the genetic differentiation between the stock enhancement strains and the first wild collection reached an intermediate level, which could lead to substructuring in wild populations. Overall, these findings revealed a potential genetic risk associated with the release of hatchery strains into wild populations.